Assessment of Physical Damages in Ukraine as a Result of the Russian Invasion through Adaptation of the Global RApid Post Disaster Damage Estimation (GRADE) Approach : Results as of March 31, 2022 - World Bank; Global Facility for Disaster Reduction and Recovery (Washington, DC, 2022)
The key objective of this report was to provide a high-level estimation of Ukraine’s physical damages following the Russian invasion on February 24, 2022, to inform the World Bank’s (WB) approach paper: relief, recovery, and resilient reconstruction-supporting Ukraine’s immediate and medium-term economic needs. This report constituted the first step of a three-phase approach for the damage and needs estimation in Ukraine as a result of the Russian Invasion. The direct physical damage estimates in this report are based on available information and data collected and assessed up to March 31, 2022. This report incorporates already published capital stock and physical damage estimates and presents the associated uncertainties in the application of the Global RApid post-disaster Damage Estimation (GRADE) approach for this assessment.